Comparison of robot-assisted thoracic surgery versus video-assisted thoracic surgery in the treatment of lung cancer: a systematic review and meta-analysis of prospective studies - Huang, Shibo; Huang, Xiaolong; Huang, Zhilong; Luo, Raoshan; Liang, Weiming (Frontiers in Oncology, 2023)
Introduction Previous studies have compared robot-assisted thoracic surgery(RATS) with video-assisted thoracic surgery (VATS) in the treatment of patients with lung cancer, but results were conflicting. The present meta-analysis aimed to compare the clinical outcomes of RATS with VATS in the treatment of patients with lung cancer. Materials and methods Web of Science, PubMed, Cochrane Library and Embase were comprehensively searched for randomized controlled trials or prospective cohort studies comparing the clinical outcomes of RATS and VATS from inception to 22 July 2023. The Cochrane Risk of Bias tool was used to assess risk of bias. Meta-analyses of length of hospital stay, postoperative duration of drainage, postoperative complications, operative time, conversion, estimated blood loss, the number of dissected lymph nodes and stations, 30-day readmission and 30-day mortality were performed. Results In total 5 studies were included in the meta-analysis. A total of 614 patients were included, of which 299 patients were treated by RATS and 315 patients treated by VATS. Blood loss was significantly less in RATS group than that in VATS (MD = −17.14, 95% CI −29.96 −4.33, P = 0.009). More nodes stations were dissected in RATS group compared with VATS group(MD= 1.07, 95% CI 0.79 1.36, P < 0.001). No significant difference occurred between RATS and VATS in length of hospital stay(MD= −0.19, 95% CI −0.98 0.61), readmission(OR=0.74, 95%CI 0.36 1.51, P=0.41), operative time(MD=11.43 95% CI −8.41 31.26, P=0.26), conversion(OR=0.58, 95% CI 0.29 1.17, P=0.13), number of dissected lymph nodes(MD=0.98, 95% CI −0.02 1.97, P=0.05), upstaging rate(OR =0.67, 95% CI 0.38 1.18, P =0.16, I2 = 0%), time of chest tube drainage (MD= −0.34, 95%CI −0.84 0.15, P=0.17), post-operative complications(OR=0.76, 95% CI 0.52 1.11, P=0.16) and total cost(MD = 3103.48, 95% CI −575.78 6782.74, P=0.1, I2 = 99%). Conclusion RATS is a feasible and safe treatment that can achieve better surgical outcomes compared with VATS in terms of short-term outcomes. Except of higher total cost, RATS has obvious advantage in lymphadenectomy and control of intraoperative bleeding. However, large sample and long follow-up randomized clinical trials comparing RATS with VATS are still necessary to better demonstrate the advantages of RATS for lung cancer. Systematic review registration https://www.crd.york.ac.uk/prospero/, Identifier CRD42023446653.